Auditory Disturbances and SARS-CoV-2 Infection: Brain Inflammation or Cochlear Affection? Systematic Review and Discussion of Potential Pathogenesis - De Luca, Pietro; Scarpa, Alfonso; Ralli, Massimo; Tassone, Domenico; Simone, Matteo; De Campora, Luca; Cassandro, Claudia; Di Stadio, Arianna (Frontiers in Neurology, 2021)
Patients affected by COVID-19 present a series of different symptoms; despite some of these are common, other less likely appear. Auditory symptoms seem to be less frequent, maybe because rarer or, alternatively, because they are underestimated during the clinical investigation. The hearing impairment might be related to the central or peripheral involvement of the auditory pathways; in particular, the likelihood of thrombosis might be one of the causes. To date, the prevalence of auditory symptoms such as sudden or progressive sensorineural hearing loss and tinnitus is unclear in COVID-19 patients. However, their presence might be an early sign of thrombosis or spread of the infection into the brain. In this systematic review of the literature we investigated the presence of auditory symptoms in COVID-19 patients and discussed their potential origin and causal relationship with SARS-CoV-2. Results showed that, despite rarely, auditory impairment can appear in patients with COVID-19 and should always be investigated for an early treatment and potential indicator of involvement of the central nervous system.